Penerapan Model Reciprocal Teaching pada Kemampuan Membaca Pemahaman Siswa Kelas IV Mata Pelajaran Bahasa Indonesia - Suroso, Nur Listiana Dwi Hutami; Setiyawan, Hery; Roosyanti, Anna (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the application of the Reciprocal Teaching model on the reading comprehension skills of grade 4 students in the Indonesian Language subject at SD Muhammadiyah 1 Menganti. The research method used is descriptive qualitative with a focus on teacher management and student activities during the learning process. Data collection is carried out through observation and documentation. The data were analyzed in a quantitative descriptive manner. The results showed that the management of learning by teachers got an average score of 3.9 (good category), which reflects the teacher's competence in managing the class. Student activities in learning got an average score of 2.9 (good category), which shows active student participation, especially in group discussions, although there are still some obstacles for students with low reading abilities. Thus, this model is effective in increasing student engagement and their understanding of the text, but additional strategies are needed to support students who experience difficulties